Parallel string-matching with variable length don't cares - Bertossi, Alan A.; Logi, Filippo (1991)
Abstract: "String matching is the problem of finding all occurrences of a pattern P in a text T, where P and T are strings over a finite alphabet [sigma]. A variable length don't care is a special character, not belonging to [sigma], which can match any string in [sigma]*. The string matching problem with variable length don't cares is an extension of the classical string matching one in which the pattern P may contain an arbitrary number of don't cares. An optimal parallel algorithm is given for solving the string matching problem with variable length don't cares. The EREW pram model of parallel computers is used to obtain an O(log n) running time using O(mn/log n) processors, where m and n are, respectively, the length of P and T
Keywords: Computer algorithms; Pattern perception